Role of serum‐ and glucocorticoid‐inducible kinases in stroke. Issue 2 (25th May 2016) - Inoue, Koichi; Leng, Tiandong; Yang, Tao; Zeng, Zhao; Ueki, Takatoshi; Xiong, Zhi‐Gang
Abstract: Increased expression of serum‐ and glucocorticoid‐inducible kinase 1 (SGK1) can be induced by stress and growth factors in mammals, and plays an important role in cancer, diabetes, and hypertension. A recent work suggested that SGK1 activity restores damage in a stroke model. To further investigate the role of SGKs in ischemic brain injury, we examined how SGK inhibitors influence stroke outcome in vivo and neurotoxicity in vitro . Infarct volumes were compared in adult mice with middle cerebral artery occlusion, followed by 24 h reperfusion, in the absence or presence of SGK inhibitors. Neurotoxicity assay, electrophysiological recording, and fluorescence Ca 2+ imaging were carried out using cultured cortical neurons to evaluate the underlying mechanisms. Contrary to our expectation, infarct volume by stroke decreased significantly when SGK inhibitor, gsk650394, or EMD638683, was administrated 30 min before middle cerebral artery occlusion under normal and diabetic conditions. SGK inhibitors reduced neurotoxicity mediated by N‐methyl‐D‐aspartate (NMDA) receptors, a leading factor responsible for cell death in stroke. SGK inhibitors also ameliorated Ca 2+ increase and peak amplitude of NMDA current in cultured neurons. In addition, SGK inhibitor gsk650394 decreased phosphorylation of Nedd4‐2 and inhibited voltage‐gated sodium currents. These observations suggest that SGK activity exacerbates stroke damage and that SGK inhibitors may be useful candidates for therapeutic intervention. To investigate the role of serum‐ and glucocorticoid‐inducible kinases (SGKs) in ischemic brain injury, we examined how SGK inhibitors influence stroke outcome. Infarct volumes induced by middle cerebral artery occlusion were decreased significantly by SGK inhibitors. The inhibitors also reduced glutamate toxicity, at least partly, by attenuation of NMDA and voltage‐gated sodium currents. Thus, SGK inhibition attenuates stroke damage. Abstract : To investigate the role of serum‐ and glucocorticoid‐inducible kinases (SGKs) in ischemic brain injury, we examined how SGK inhibitors influence stroke outcome. Infarct volumes induced by middle cerebral artery occlusion were decreased significantly by SGK inhibitors. The inhibitors also reduced glutamate toxicity, at least partly, by attenuation of NMDA and voltage‐gated sodium currents. Thus, SGK inhibition attenuates stroke damage.